(untitled) (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2022)
Introduction: Children of primary school age are prone to nutritional problems, one of which is over nutrition. Globally, the prevalence of over nutrition children increased by around 47.1%, while in Indonesia it increased to 10.8% and 9.2%. The main cause of over nutrition in children is the wrong diet which is influenced by the family and school environment. Family plays a role in forming healthy eating behavior, one of which is to get breakfast habits. The school also plays a role in providing healthy food for children while they are at school. Purpose: To know the description of breakfast habits and snack habits at school coffee breaks in children with over nutrition at SDIT Al-Hikmah Maros. Materials and Methods: Descriptive research design. The sample was students in grades 4-6 who had